Single-cell approaches reveal novel cellular pathways for megakaryocyte and erythroid differentiation - Psaila, B; Mead, A (American Society of Hematology, 2019)
The classical model of hematopoiesis proposes a hierarchy in which a small number of multipotent hematopoietic stem cells (HSCs) maintain all blood lineages by giving rise to progeny that pass through discrete progenitor stages. At each stage, lineage differentiation potential is restricted, coupled with the loss of ability to self-renew. Recently, single-cell approaches have been used to test certain assumptions made by this model, in particular relating to megakaryocyte (Mk) and erythroid (E) development. An alternative model has emerged in which substantial heterogeneity and lineage-priming exists within the HSC compartment, including the existence of multipotent but megakaryocyte/platelet-biased HSCs. Hematopoietic differentiation follows a hierarchical continuum, passing through cellular nodes and branch points. Megakaryocytes are produced via a shared pathway with the erythroid lineage, also shared in its early stages with mast cells, eosinophils, and basophils, but separate from other myeloid and lymphoid lineages. In addition, distinct pathways for direct differentiation of Mk from HSCs may coexist and could be important in situations of increased physiological requirements or in malignancies. Further work at single-cell resolution using multiomic approaches and examining Mk-E biased subsets within their physiological context will undoubtedly improve our understanding of normal hematopoiesis and ability to manipulate this in pathology.